CARBON EMISSIONS, ECONOMIC GROWTH, AND RENEWABLE ENERGY IN INDONESIA: AN AUTOREGRESSIVE DISTRIBUTED LAG MODEL - Perwithosuci, Winny; Kurniawan, Mahrus Lutfi Adi; Kuncoro, Trian Gigih (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This research aims to analyze the effect of economic growth, foreign direct investment (FDI), oil consumption, and hydroelectricity generation on emission in Indonesia from 1986-2022. The data are generated from World Bank and British Petroleum. This study employs Autoregressive Distributed Lag (ARDL) to estimate the secondary data. Carbon dioxide emissions (CO2) is treated as dependent variable, while economic growth, FDI inflows, oil consumption, and hydroelectricity generation are treated as independent variables. The results revealed that economic growth positively affect CO2 in the short run. Foreign Direct Investment (FDI) affect CO2 negatively but not significant on CO2. The result implies that the Pollution Halo is exist. Oil consumption affect CO2 positively significant both in short and long run. Furthermore, hydroelectricity generation as renewable energy affects CO2 negatively in the short run and positively in the long run but not significant. The result suggests to the stakeholders to enhance the innovation of the renewable energy to decline the CO2 emssions. Further, this study surely provides a new model in estimating the determinant of CO2 emissions as a proxy of environmental degradation especially in Indonesia.